Australian spore-feeding Thysanoptera of the genus Bactrothrips (Phlaeothripidae – Idolothripinae) - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2011)
Six species, including four new species, are recognised from Australia in Bactrothrips, and Lasiothrips Moulton is synonymised with this genus. This group of spore-feeding thrips is widespread on dead leaves across the Old World tropics from Africa to Japan. The Australian species are mainly associated with dry fruiting capsules of Eucalyptus trees. Males usually have lateral tubercles on the abdomen, but no fore tarsal teeth, and the significance of this in sexual behaviour is noted.